Bovine leukemia virus long terminal repeat variability: identification of single nucleotide polymorphisms in regulatory sequences - Pluta, Aneta (Virol J, 2018)
BACKGROUND: Limited data are available on the incidence of variations in nucleotide sequences of long terminal repeat (LTR) regions of Bovine Leukemia Virus (BLV). Consequently, the possible impact of SNPs on BLV LTR function are poorly elucidated. Thus, a detailed and representative study of full-length LTR sequences obtained from sixty-four BLV isolates from different geographical regions of Poland, Moldova, Croatia, Ukraine and Russia were analyzed for their genetic variability. METHODS: Overlap extension PCR, sequencing and Bayesian phylogenetic reconstruction of LTR sequences were performed. These analyses were followed by detailed sequence comparison, estimation of genetic heterogeneity and identification of transcription factor binding site (TFBS) modifications. RESULTS: Phylogenetic analysis of curated LTR sequences and those available in the GenBank database reflected the acknowledged env gene classification of BLV into 10 genotypes, and further clustered analysed sequences into three genotypes - G4, G7 and G8. Additional molecular studies revealed the presence of 97 point mutations distributed at 89 positions throughout all 64 LTR sequences. The highest rate of variability was noted in U3 and U5 subregions. However, the variability in regulatory sequences (V(R)) was assessed as lower than the variability within non-regulatory sequences (V(NR)) for both, U3 and U5 subregions. In contrast, V(R) value for R subregion, as well as for the total LTR, was higher than the V(NR) suggesting the existence of positive selection. Twelve unique SNPs for these LTR sequences localized in regulatory and non-regulatory elements were identified. The presence of different types of substitutions lead to the abrogation of present or to the creation of additional TFBS. CONCLUSION: This study represents the largest study of LTR genetic variability of BLV field isolates from Eastern part of Europe. Phylogenetic analysis of LTRs supports the clustering BLV variants based on their geographic origin. The SNP screening showed variations modifying LTR regulatory sequences, as well as altering TFBS. These features warrant further exploration as they could be related to proviral load and distinctive regulation of BLV transcription and replication. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12985-018-1062-z) contains supplementary material, which is available to authorized users.